College physics - Urone, Paul Peter (Brooks/Cole, 2001)
In the new Second Edition of College Physics, Peter Urone succeeds in carrying out several goals: to convey the concepts of physics and to help students build the analytical skills to apply them; to help students gain an appreciation for the underlying simplicity and unity in nature; and to impart a sense of the beauty and wonder found in the physical universe. To accomplish these goals, Urone blends coverage of the traditional topics with modern material; and familiar ideas from modern physics, such as the existence of atoms and the conversion of mass into energy, are incorporated early. Topics are introduced conceptually with a steady progression to precise definitions and analytical applications. The analytical aspect (problem solving) is tied back to the concept before moving on to another topic. Urone uses a four-part example and problem-solving mechanism to improve students' skills in solving problems, as well as understanding underlying concepts.